Anatomy of the mouse penis and internal prepuce - Cunha, Gerald R. (Differentiation, 2020)
This paper addresses a confusing issue of preputial anatomy of the mouse. The term “internal prepuce” was used in 2013 to describe a preputial structure integral to the mouse glans penis. Subsequently in 2015 the same term was applied by another group to describe entirely different morphology, generating confusion in the literature. Because it is inappropriate to use the same term to describe entirely different structures, we take this opportunity to provide further descriptive information on the internal prepuce of the mouse employing gross dissection, analysis of serial histologic section sets, three-dimensional reconstruction, scanning electron microscopy and immunohistochemistry. For this purpose, we review and illustrate the relevant literature and provide some additional new data using standard morphological techniques including immunohistochemistry. The mouse internal prepuce is integral to the glans penis and clearly is involved in sexual function in so far as it contains a major erectile body innervated by penile nerves. The development of the mouse internal prepuce is described for the first time and related to the development of the corpus cavernosum glandis.